Breaking Barriers: Enhancing Support for Autistic Students Through Individual Education Programs - Ola-Williams, Maureen Chinasa; Ola-Williams, Adeyinka; Ogbaini, Clement Aliu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The prevalence of Autism Spectrum Disorders (ASD) underscored the importance of tailoring educational interventions to accommodate the diverse needs of autistic students in Nigeria. This study investigated the effectiveness of individual educational programs in meeting the needs of autistic students in Nigeria. The study surveyed autistic children, teachers, and parents in special schools in Ikeja, Apapa, and Kosofe Local Government Areas of Lagos State. It used a mixed-methods approach to evaluate the effectiveness of Individual Education Programs (IEPs) in addressing the unique needs of autistic students in mainstream educational settings. The study analyzed academic performance metrics and social skills proficiency in autistic students. It also explored the experiences of teachers, parents, and autistic students through interviews and focus groups. Despite challenges like lack of resources and collaboration issues, teachers shared success stories and strategies. Parents praised positive efforts between home and school, while autistic students expressed improved learning experiences. The synthesis of quantitative and qualitative data provided a holistic evaluation of IEPs' effectiveness in promoting positive outcomes for autistic students. The findings contribute to the discourse on inclusive education, informing practices to refine IEP design and implementation. The study emphasizes providing meaningful educational support tailored to the diverse needs of autistic students in mainstream settings.